(3x+3)(3x+3)=

Simple and best practice solution for (3x+3)(3x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+3)(3x+3)= equation:


Simplifying
(3x + 3)(3x + 3) = 0

Reorder the terms:
(3 + 3x)(3x + 3) = 0

Reorder the terms:
(3 + 3x)(3 + 3x) = 0

Multiply (3 + 3x) * (3 + 3x)
(3(3 + 3x) + 3x * (3 + 3x)) = 0
((3 * 3 + 3x * 3) + 3x * (3 + 3x)) = 0
((9 + 9x) + 3x * (3 + 3x)) = 0
(9 + 9x + (3 * 3x + 3x * 3x)) = 0
(9 + 9x + (9x + 9x2)) = 0

Combine like terms: 9x + 9x = 18x
(9 + 18x + 9x2) = 0

Solving
9 + 18x + 9x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '9'.
9(1 + 2x + x2) = 0

Factor a trinomial.
9((1 + x)(1 + x)) = 0

Ignore the factor 9.

Subproblem 1

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Solution

x = {-1, -1}

See similar equations:

| F(4)=10-2x | | F(4)=4x-3 | | 2x^4+9x^2+2=0 | | 7-8=x | | 17=1+x-5x | | 7m+2=58,7 | | 3(4+x)=8-2x | | 6+8(1+x)=-x-40 | | (s+7)(s-5)= | | 5a+6b=4a-3 | | 3u-2=3u+2 | | (7t^2-t-9)(3t^2+7t-1)= | | 1g-s=-8a+3 | | 1.8*1.5= | | s=169cm | | (17/5)+4x=5x-(18/5) | | x+x+9=2x-9 | | 4w+5=4w+8 | | 1/3x=1-1/2y | | 2x(x-18)=0 | | x+3y=128 | | 35+5w+25y= | | 5-3m=13 | | x-4+25/5 | | -8+2m=-6(m+2) | | 3x(x-5)-2(x-2)(x+2)=(x+4)(x+1)-16 | | x=1000-20y-50z | | -2y-6=3y+19 | | 4x+9y=23 | | .1x+2y+5z=100 | | F(x)=2x-11 | | 8x+1.5xy=300 |

Equations solver categories